Pengaruh Konten Video Kondisi Palestina Dalam Akun Instagram LAZDAU Terhadap Engagement Audiens - Kirana Rizqina; Aris Sutejo (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
In the digital era, it's not unusual for us to spend time on social media such as Instagram, Youtube, and TikTok. Since the covid 19 virus broke out in 2020, video content has become more popular than ever, especially short-duration videos. Therefore, many entities are using video content to build their image or promote their brand. LAZDAU as a philanthropic organization can certainly do the same to achieve their goal, which is to help distribute aid to those in need. Therefore, the research on the influence of video content on social media will be specifically aimed at the Reels content on LAZDAU's Instagram account and the correlation with the number of feedbacks they receive